Vertical Growth of Core-Shell III-V Nanowires for Solar Cells Application - Kim, D. Y.; Bae, M. H.; Shin, J. C.; Kim, Y. J.; Lee, Y. J.; Choi, K. J.; Seong, T. Y.; Choi, W. J. (AMER SCIENTIFIC PUBLISHERS, 2014)
High density (In)GaAs/GaAs/AlGaAs nanowires (NWs) consisting of n-type core and p-type shell have been vertically grown on (111) GaAs substrate using metal organic chemical vapor deposition (MOCVD) and fabricated into solar cells. Au colloidal nanoparticles (NPs) are employed as a catalyst. High density nanowires were obtained by uniform distribution of Au NPs. Fe-SEM, TEM and HRTEM images show that the morphology of shell is sensitive to p-doping concentration. Increase in the density of p-doping precursor results in "kinking" of NPs and rough shell surface. The origin of kinking has been explained by the GaAs twin phases due to Zn segregation on the surface of shell. It has been observed that the morphology of NPs can be controlled through optimizing various source purge technique of DEZn and deposition temperature. Electrical properties of core shell doped NWs are carried out using I V characterization. The core shell NWs show characteristics of p-n junction as revealed by I-V studies.
Keywords: SEMICONDUCTOR NANOWIRES; SUPERLATTICES